Feather steroid hormone concentrations in relation to age, sex, and molting time in a long‐distance migratory passerine - Marie Adámková; Zuzana Bílková; Oldřich Tomášek; Zdeněk Šimek; Tomáš Albrecht (Ecology and Evolution)
Abstract In birds, concentrations of testosterone (T) and corticosterone (Cort) are closely connected with many morphological, behavioral, and other physiological traits, including reproduction, metabolism, immunity, and fitness. The direction of the effect of these hormones on above‐mentioned traits, and the potential feedback between hormones are in general unclear; in addition, knowledge on how age and sex can affect T and Cort concentrations is still inconsistent. Our study used a novel method to analyze testosterone and corticosterone in feathers (Tf, Cortf) based on the precolumn chemical derivatization of hormones before liquid chromatography–tandem mass spectrometry (LC‐MS/MS) analysis. Unlike previously used methods (RIA, EIA), our analytical procedure allows simultaneous analysis of both hormones from small amounts of feathers (4–25 mg) and, thus, overcomes the problem of insufficient detection limits. We applied this method to reveal associations between Tf and Cortf hormone concentrations and feather growth, age, and sex in feathers grown during the postbreeding (flanks) and prebreeding (tails) periods in barn swallows (Hirundo rustica). There was neither a correlation between prebreeding and postbreeding Tf, nor between prebreeding and postbreeding Cortf. Tail Cortf concentrations were negatively associated with tail feather growth rates. Feather hormone concentrations were correlated in the prebreeding period, negatively in males but positively in females. Both Cortf and Tf were higher in young birds compared to older ones, indicating either an age‐related decrease in hormone concentrations within individuals, or the selective disappearance of individuals with high steroid concentrations. Males and females did not differ in Cortf, but Tf concentrations were higher in males than females, particularly during the prebreeding period. In this study, we provide an effective method for analyzing hormones in feathers in an ecological context, especially in situations when the total amount of feathers available for the analysis is limited.